2016
DOI: 10.1590/1807-1929/agriambi.v20n1p42-48
|View full text |Cite
|
Sign up to set email alerts
|

Soil chemical properties and maize yield under application of pig slurry biofertilizer

Abstract: Organic materials subjected to a process of anaerobic digestion in a digester produce biofertilizer that can be used in agriculture as nutrient source. The objective of this study was to evaluate the effect of pig slurry biofertilizer on soil chemical properties and on corn yield and nutrient concentrations in leaves and kernels. The experiment was conducted in the field from November 2012 to April 2013, and was arranged in a randomized block design with seven treatments and four replicates. The treatments con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
2
5
0
6
Order By: Relevance
“…The foliar contents of N, P, K, Ca, Mg, S, Fe, Mn, Cu and Zn in soybeans were not affected (p > 0.05) by treatments (Table 3). Similar results were obtained by Santos et al (2012), Sediyama et al (2014), Seidel et al (2010) and Bócoli et al (2016), which detected no changes in foliar concentrations of N, P and K in squash, peppers and corn, respectively, with the application of pig manure. However, Corrêa et al (2008) noted that, with increasing doses of organic waste, N content increased in soybean leaves.…”
Section: Resultssupporting
confidence: 88%
“…The foliar contents of N, P, K, Ca, Mg, S, Fe, Mn, Cu and Zn in soybeans were not affected (p > 0.05) by treatments (Table 3). Similar results were obtained by Santos et al (2012), Sediyama et al (2014), Seidel et al (2010) and Bócoli et al (2016), which detected no changes in foliar concentrations of N, P and K in squash, peppers and corn, respectively, with the application of pig manure. However, Corrêa et al (2008) noted that, with increasing doses of organic waste, N content increased in soybean leaves.…”
Section: Resultssupporting
confidence: 88%
“…Compared with the NPK fertilization recommended for maize (Souza & Lobato, 2004): the LSW dose of 200 m 3 ha -1 exceeded in relation to N; none of the doses met the requirements of P; and LSW doses above 100 m 3 ha -1 were superior in relation to K. Swine wastes can be considered as unbalanced fertilizers, since they have nutrients in disproportionate amounts in relation to the requirements of the plants (Berwanger, 2006), as opposed to mineral fertilizers, which can be specifically formulated, according to the conditions of cultivation and soil. Hence, excessive or successive fertilizations with swine waste can cause alterations in soil chemical attributes (Scherer et al, 2010;Lourenzi et al, 2013) and lead to undesirable environmental impacts, such as pollution of surface and subsurface waters (Carneiro et al, 2012;Sørensen & RubAEk, 2012;Sweeney et al, 2012).…”
Section: Resultsmentioning
confidence: 93%
“…Kunz and Oliveira (2008) stated that the goal of biodigestors in Brazil is: the treatment of effluents, use of biogas as an energy alternative, and the use of effluent to improve soil fertility. The use of these effluents to recover water and improve fertility was also an objective described by Leal et al (2010) and Bócoli et al (2016). Silva (2012) concluded that biodigestion of human and swine waste was feasible, reducing BOD, COD and coliform levels; however, the treated effluent cannot be directly discharged in water bodies, without prior clearance.…”
Section: Resultsmentioning
confidence: 99%